St. Louis Paper - Oil Shales and Petroleum Prospects in Brazil (with Discussion) - H. E. Williams (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1921)
In view of the frequent occurrence of petroleum in other parts of the world, it seems odd that so large an area as is contained within the borders of Brazil should be without this product. This apparent deficiency may be due, however, to our ignorance of the regions in which it may exist. In some places, indications point to the probable existence of petroleum in ages gone by; and while the presence of petroleum pools may be problematic, in several regions conditions not unfavorable to their occurrence exist. Yet, Brazil has enormous oil resources in the rich oil-shales in different parts of the country. Many of these shales are very rich and only suitable processes for the extraction of the oil are lacking. At the present time, only a few small experimental plants are producing oil by distillation from these shales. These plants have been the subject of recent investigations by the Geological and Mineralogical Survey, a preliminary report of which is in the hands of the printer. The only regions where studies have not been made are the upper Amazon, the Acre, the Rio Negro, and the Peruvian frontier, which really seems to be the most promising field for explorations of any in the country. In the vast plateau region of the interior north of the 20th parallel of latitude, granites, gneiss, mica schists, and very old metamorphosed sedimentaries predominate. Later, sedimentaries occupy a minor position and, where found in the interior, represent a thin veneering resting on the older rocks. At several places near the coast they have a greater development and contain considerable beds of oil-shale and may, .in some cases, offer conditions favorable for the occurrence of oil. Such deposits are found in the Permian rocks of central and southern Maran-hao; in the Tertiary and Cretaceous beds along the coast of Alagsas Sergipe, Bahia, and perhaps farther south in Espirito Santo; and in the Parahyba embayment north of Cape Frio and in the interior Tertiary basin of eastern Sao Paulo.